Compositional attributes and fatty acid profile of lamb meat from Iberian local breeds - Cadavez, Vasco (2018)
This study aimed to compare lamb meat composition from five Iberian breeds raised in their typical rearing systems and to reveal trends in compositional meat attributes due to breed or production system. The meat quality of 153 animals was analysed. The combined effect of breed × production system produced significant differences in lamb meat quality. Meat from the extensively-reared Bordaleira-de-Entre-Douro-e-Minho (BEDM) and Gallega breeds had elevated amounts of n-3 PUFAs, tocopherol content and favourable n-6/n-3 ratio. Meat from lambs grown under extensive and semi-extensive systems presented higher content of conjugated linoleic acid than the two breeds reared intensively. The meat of commercial breed (INRA401) was characterised by higher content of protein and MUFAs and lower atherogenic potential than the breeds reared in extensive and semi-extensive systems. Principal component analysis demonstrated that meat from extensively raised lambs was associated to higher SFA, CLA, α-tocopherol, n-3, atherogenic index and cholesterol content, but lower intramuscular fat and retinol content, MUFA and n-6/n-3.